Superordination and subordination in international relations – geopolitics of hegemony and subjection (Economic and Political Thought, 2016)
The starting point for the analysis is the relationship between geopoliticsand globalization, which seem to be crucial in explaining the contemporaryinternational reality. Great superpowers, which are the pillars of globalizationprocesses, promote their values, but at the same time miss no opportunityand do not lose their willpower to enter new domains of influence, oftenat the expense of their partners or contractors. A major change in understandingworld geopolitics lies in the fact that the centre of gravity of poweris shifting from the West to the East and South. Simultaneously, a “greatreconvergence” of the East and the West is underway, involving efforts tocreate a counterweight to the U.S. by such powers as China or Russia. Allthis means that the post-Cold War international order is still in transition,and it is marked by polycentrism and interpolarity, and even a decline ofpolarity understood traditionally. With regard to the scale of power, there isa hierarchical and heterarchical diversity of participants, while the principlesthat govern the functioning of the international system as a whole are coordinationand its derivatives – superordination and subordination.